The effects of the location of cancer stem cell marker CD133 on the prognosis of hepatocellular carcinoma patients - Yao-Li Chen; Ping-Yi Lin; Ying-Zi Ming; Wei-Chieh Huang; Rong-Fu Chen; Po-Ming Chen; Pei-Yi Chu (BMC Cancer, 2017)
Abstract Background CD133 (prominin-1) is widely believed to be a cancer stem cell marker in various solid tumor types, and CD133 has been correlated with tumor-initiating capacity. Recently, the nuclear location of CD133 expression in tumors has been discussed, but hepatocellular carcinoma (HCC) has not been included in these discussions. The goal of this study was to investigate the location of CD133 expression in HCC and this location’s potential value as a prognostic indicator of survival in patients with HCC. Methods We enrolled 119 cancerous tissues and pair-matched adjacent normal liver tissue from HCC patients. These tissues were obtained immediately after operation, and tissue microarrays were subsequently constructed. The expression of CD133 was measured by immunohistochemistry (IHC), and the correlations between this expression and clinical characteristics and prognosis was estimated using statistical analysis. Results The results showed that the CD133 protein expression levels of HCC in both the cytoplasm and nucleus were significantly higher than adjacent normal liver tissue. Kaplan–Meier survival and Cox regression analyses revealed that high CD133 expression in the cytoplasm was an independent predictor of poor prognosis for the overall survival (OS) and relapse-free survival (RFS) rates of HCC patients (P = 0.028 and P = 0.046, respectively). Surprisingly, high nuclear CD133 expression of HCC was an independent predictor of the good prognosis of the OS and RFS rates of HCC patients (P = 0.023 and P = 0.012, respectively). Conclusions The clinical evidence that revealed cytoplasmic CD133 expression was correlated with poor prognosis, while nuclear CD133 expression was significantly correlated with favorable prognosis.